2014
DOI: 10.5152/eurjrheumatol.2014.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C infections in rheumatoid arthritis and ankylosing spondylitis: A multicenter countrywide study

Abstract: Objective: Immunosuppressive therapies, especially tumor necrosis factor-α inhibitors, are frequently used in treatment of rheumatoid arthritis (RA) and ankylosing spondylitis (AS). These therapies can induce viral reactivation in concurrent hepatitis B virus (HBV)-or hepatitis C virus (HCV)-positive patients. On the other hand, the prevalence of HBV and HCV infections is not exactly known in RA and AS patients. The aim of this study was to investigate the prevalence of HBV and HCV infections in RA and AS pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
4
11
0
5
Order By: Relevance
“…Similar to our results, findings from a Brazilian study where RA existed in 2.6% of patients with current HBV infection [10]. On the national level, a study conducted at Assiut University Hospital revealed similar findings; a 2% prevalence of HBV infection among RA patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, findings from a Brazilian study where RA existed in 2.6% of patients with current HBV infection [10]. On the national level, a study conducted at Assiut University Hospital revealed similar findings; a 2% prevalence of HBV infection among RA patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…The fact that the HCV-uninfected cohort had the lowest cumulative incidence of rheumatic diseases, and HCV infection increased the HR of developing rheumatic diseases based on multivariate analyses, endorsed the concept that HCV infection might cause rheumatic diseases, despite the fact that some studies did not support the participation of HCV infection in the pathogenesis of RA [ 29 , 30 , 31 ]. However, given that the HRs in developing rheumatic diseases between the HCV-treated and HCV-untreated cohorts were indifferent, the HCV-associated risk of rheumatic diseases might not be attenuated by interferon-based anti-HCV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The facts that the HCV-uninfected cohort had the lowest cumulative incidence of rheumatic disorders, and HCV infection increased the HR of developing rheumatic disorders based on multivariate analyses endorsed the concept that HCV infection might cause rheumatic disorders, despite some studies did not support the participation of HCV infection in the pathogenesis of RA [25][26][27]. However, given that the HRs in developing rheumatic disorders between the HCV-treated and HCV-untreated cohorts were indifferent, the HCV-associated risk of rheumatic disorders might not be attenuated by interferon-based anti-HCV therapy.…”
Section: Discussionmentioning
confidence: 99%